Development of DEXS: A Simple GNU Octave-Based Software for Very Low Frequency Electromagnetic (VLF-EM) Data Processing - Lestari, Dwi Santi; Susilawati, Anggie; Manalu, Xena Wilhelmina; Nurinsani, Muhamad Santri; Taura, Muhammad Enzy; Rachayu, Meylani Shintia; Aryangga, Kensi (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2027)
Very Low Frequency Electromagnetic (VLF-EM) data processing currently faces two major challenges: limited accessibility due to the high licensing costs of commercial software and the limited capabilities of existing software. This study aims to develop a simple software package, named DEXS, featuring a Graphical User Interface (GUI) on the GNU Octave platform as a freely accessible open-source alternative. DEXS was developed as a single .m script and designed to integrate the entire VLF-EM data processing workflow within a unified interface, including data import, averaging of repeated measurements at each station, application of the Fraser Filter and Karous–Hjelt Filter, and visualization of results in the form of graphs and two-dimensional pseudo-section maps. The software was evaluated using two VLF-EM field datasets by comparing the outputs generated by DEXS with those produced by KHFILT. The results show that the Fraser Filter graphs, Karous–Hjelt graphs, and pseudo-section maps generated by DEXS exhibit anomaly patterns that are consistent and comparable with those produced by KHFILT. Quantitative validation using cross plot analysis yielded a very strong linear relationship (R² > 0.999), confirming that the implemented algorithms are mathematically consistent and valid for qualitative subsurface structure interpretation. DEXS also provides more comprehensive capabilities than KHFILT, including support for six-column measurement parameter input, simultaneous visualization of two survey lines, and additional displays of out-phase and field strength data. These capabilities contribute to the development of open-source geophysical software by providing an integrated, validated, and freely accessible VLF-EM data processing system that supports both educational and research applications.